Bovine Lactoferrin-Induced CCL1 Expression Involves Distinct Receptors in Monocyte-Derived Dendritic Cells and Their Monocyte Precursors - Daniela Latorre; Nadia Pulvirenti; Daniela Angela Covino; Barbara Varano; Cristina Purificato; Gabriella Rainaldi; Maria Cristina Gauzzi; Laura Fantuzzi; Lucia Conti; Gloria Donninelli; Manuela Del Cornò; Michela Sabbatucci; et al. (Toxins, 2015)
Lactoferrin (LF) exhibits a wide range of immunomodulatory activities including modulation of cytokine and chemokine secretion. In this study, we demonstrate that bovine LF (bLF) up-modulates, in a concentration- and time-dependent manner, CCL1 secretion in monocytes (Mo) at the early stage of differentiation toward dendritic cells (DCs), and in fully differentiated immature Mo-derived DCs (MoDCs). In both cell types, up-modulation of CCL1 secretion is an early event following bLF-mediated enhanced accumulation of CCL1 transcripts. Notably, bLF-mediated up-regulation of CCL1 involves the engagement of distinct surface receptors in MoDCs and their Mo precursors. We show that bLF-mediated engagement of CD36 contributes to CCL1 induction in differentiating Mo. Conversely, toll-like receptor (TLR)2 blocking markedly reduces bLF-induced CCL1 production in MoDCs. These findings add further evidence for cell-specific differential responses elicited by bLF through the engagement of distinct TLRs and surface receptors. Furthermore, the different responses observed at early and late stages of Mo differentiation towards DCs may be relevant in mediating bLF effects in specific body districts, where these cell types may be differently represented in physiopathological conditions.